PLOS global public health (Public Library of Science, 2021)
PLOS Global Public Health addresses deeply entrenched global inequities in public health and makes impactful research visible and accessible to health professionals, policy-makers, and local communities without barriers.
Keywords: právo na zdraví; Health Services Accessibility; veřejné zdravotnictví; celosvětové zdraví; Right to Health; Public Health; dostupnost zdravotnických služeb; Global Health